Review: The harvesting process and recent advances on health benefits of white tea - Mastur, Adhi Irianto; Karuniawan, Agung; Ernah, Ernah (Universitas Padjadjaran, 2023)
The meticulous harvesting process and appropriate post-harvest techniques play pivotal roles in preserving the quality and health benefits of white tea. This careful approach maintains the bioactive compounds such as polyphenols, caffeine, gallic acid, Epigallocationchin (EGC), Epigallocationchin gallate (EGCG), and Epicatechin gallate (ECG), integral to white tea's health benefits. The stability of catechin content in tea plants is greatly influenced by the environment (clone, plant age, leaf age, altitude, temperature, humidity, processing, and pH when storing dry tea). In Indonesia, the raw materials used to produce white tea are mostly pecco from the superior GMB clone Assamica variety which has high polyphenol content (14.83 – 15.43% dry weight). To increase polyphenol levels, the treatment that needs to be considered is the provision of optimum and appropriate fertilizer. The highest catechin content comes from plucking in summer and spring season. Subsequently, controlled post-harvest processes, including controlled withering and drying, safeguard the integrity of active compounds like catechins as antioxidants in white tea, mitigating free radicals and cellular damage. The highest antioxidant showed from 23 hours whithered. The storage time for white tea also has an impact on quality. The content of catechins and amino acids showed a tendency to decrease with storage time. On the other hand, gallic acid increases with the length of storage. The combined effect of these phases, from harvesting through post-harvesting, contributes significantly to white tea's health benefits, encompassing cardioprotective effects, anti-diabetic potential, prevention of anticarcinogenic and antimutagenic activity, neuroprotective properties, and antimicrobial attributes.